Covid-19 Pandemic: Is there any impact on the Agribusiness Index? - Lumbanraja, Penny Chariti; Lumbanraja, Pretty Luci; Pandiangan, Saut Maruli Tua (Research of Finance and Banking, 2024)
This study aims to determine if there was an increase in financial performance among companies in the Agri sector listed on the Indonesia Stock Exchange during the COVID-19 pandemic. A quantitative descriptive approach was used, analyzing secondary data from financial reports of Agri index companies for 2019 (pre-pandemic) and 2020 (during the pandemic). The research variables include the liquidity ratio (current ratio), leverage (debt-to-equity ratio), profitability (return on assets), and activity ratio (receivable turnover). The study found both increases and decreases in the financial performance of the sample companies across these variables. The findings provide insights for investors and stakeholders regarding the opportunities and risks in Indonesia's Agribusiness sector during the pandemic.